2014
DOI: 10.2527/jas.2013-7441
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation based on protein or energy ingredients to beef cattle consuming low-quality cool-season forages: I. Forage disappearance parameters in rumen-fistulated steers and physiological responses in pregnant heifers1

Abstract: Two experiments evaluated the influence of supplement composition on ruminal forage disappearance, performance, and physiological responses of Angus × Hereford cattle consuming a low-quality cool-season forage (8.7% CP and 57% TDN). In Exp. 1, 6 rumen-fistulated steers housed in individual pens were assigned to an incomplete 3 × 2 Latin square design containing 2 periods of 11 d each and the following treatments: 1) supplementation with soybean meal (PROT), 2) supplementation with a mixture of cracked corn, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
2
6
0
1
Order By: Relevance
“…Another study supplemented primiparous beef cattle fed an annual rye hay with soybean meal during the final trimester and for 58 d following parturition (Hess et al, 1998) and found that serum urea nitrogen concentrations tended to be elevated, and milk urea nitrogen concentrations with increased with protein supplementation post-partum (Hess et al, 1998). Similarly, plasma urea concentrations increased when gestating beef cattle were fed a soybean meal supplement vs. cows fed the basal diet containing 8.7% CP diet (Cappellozza et al, 2014). The researchers postulated that the elevated serum urea nitrogen was attributed to enhanced ruminal protein breakdown resulting in increased ammonia absorption by the rumen (Cappellozza et al, 2014).…”
Section: Protein Supplementation's Influence On Circulating Metabolites and Markers Of Protein Synthesis And Degradationmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study supplemented primiparous beef cattle fed an annual rye hay with soybean meal during the final trimester and for 58 d following parturition (Hess et al, 1998) and found that serum urea nitrogen concentrations tended to be elevated, and milk urea nitrogen concentrations with increased with protein supplementation post-partum (Hess et al, 1998). Similarly, plasma urea concentrations increased when gestating beef cattle were fed a soybean meal supplement vs. cows fed the basal diet containing 8.7% CP diet (Cappellozza et al, 2014). The researchers postulated that the elevated serum urea nitrogen was attributed to enhanced ruminal protein breakdown resulting in increased ammonia absorption by the rumen (Cappellozza et al, 2014).…”
Section: Protein Supplementation's Influence On Circulating Metabolites and Markers Of Protein Synthesis And Degradationmentioning
confidence: 99%
“…Similarly, plasma urea concentrations increased when gestating beef cattle were fed a soybean meal supplement vs. cows fed the basal diet containing 8.7% CP diet (Cappellozza et al, 2014). The researchers postulated that the elevated serum urea nitrogen was attributed to enhanced ruminal protein breakdown resulting in increased ammonia absorption by the rumen (Cappellozza et al, 2014). This allowed for increased urea formation in the liver, promoting urea transport into the blood.…”
Section: Protein Supplementation's Influence On Circulating Metabolites and Markers Of Protein Synthesis And Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the supplementation strategies available, mineral and/or protein-energy supplementation are often adopted in pasture-based systems. As an example, Fieser et al (2007) and Cappellozza et al (2014a , 2014b ) demonstrated that mineral only and protein-energy supplementation improved the performance of beef steers and heifers, respectively, compared with nonsupplemented cohorts. Nonetheless, the intake of salt-based mineral supplements is extremely variable among animals, year, and season ( Arthington and Swenson, 2004 ), but research in this area is very limited.…”
Section: Introductionmentioning
confidence: 99%